Investigating the enzyme-lignin binding with surfactants for improved saccharification of pilot scale pretreated wheat straw. (January 2017) - Agrawal, Ruchi; Satlewal, Alok; Kapoor, Manali; Mondal, Sujit; Basu, Biswajit
Graphical abstract: Highlights: 21 surfactants evaluated for the impact on pretreated biomass saccharification. Selected surfactant enhanced saccharification of steam exploded biomass by 55% and dilute acid pretreated biomass by 26%. Mechanism of surfactant action investigated. Surfactant supplementation is an effective strategy to achieve higher saccharification and reducing enzyme dosage. Abstract: In this study, commercial surfactants have been investigated at economically viable dosage to enhance the enzymatic saccharification of pretreated wheat straw at high solid loadings. Twenty one surfactants were evaluated with pilot scale pretreated wheat straw and mechanism of surfactant action has been elucidated. One surfactant has improved the saccharification of dilute acid wheat straw (DAWS) by 26.4% after 24 h and 23.1% after 48 h while, steam exploded wheat straw (SEWS) saccharification was increased by 51.2% after 24 h and 36.4% after 48 h at 10% solid loading. At 20% solid loading, about 31% increase in yield was obtained on DAWS and about 55% on SEWS after 48 h. Further, lignin was isolated from pretreated wheat straws and characterized which revealed that SEWS derived lignin was more hydrophobic than DAWS lignin. This investigation suggests that surfactant supplementation during saccharification is an effective strategy to achieve higher saccharification yield.